Islamic Religious Education With Peace Education - Luthfi Hibatullah (AIUA Journal of Islamic Education, 2020)
The current wave of unrelenting violence around the world has prompted researchers to investigate the intersection of education and peace to better understand this relationship. Achieving peace is a humanizing process in which individuals manage their violent tendencies. Peace education contributes to this process by teaching about peace. Peace education teaches about how conflict begins, the effect of violent solutions to conflict, and alternatives to violent behavior. Peace education students learn how to resolve nonviolent disputes. Students also learn quietly educational classes about peace strategies that can be used both micro and macro. Peace education is known as environmental education that explains the principles of sustainable living.